Zur Herkunft der Inschrift ICUR 3900: Basilica Apostolorum oder titulus Apostolorum (S. Pietro in Vincoli)? - Vollmer, Cornelius (Römische Mitteilungen, 2024)
The inscription ICUR 3900 is passed down only literally in a 9th century codex but without a remark of its original derivation. Its contextual tradition together with inscriptions from churches in Rome makes an attribution to a church in Rome very likely, probably a church in which the Apostles Peter and Paul were venerated because of its beginning hic Petrus et Paulus… For this ICUR 3900 is mostly attributed to the Basilica Apostolorum at the Via Appia (S. Sebastiano) and the anonymous persons in the inscription marked praesul, filius, genitor and involved in the edification of the church were tentatively tried to uncover. This article brings forward several arguments for an attribution of ICUR 3900 to the archaeologically proved first building phase of the titulus Apostolorum (S. Pietro in Vincoli) around 400. The founder of the church – in the inscription the praesul corresponding obviously with the genitor – could therefore be Pope Anastasius I (399–401) and the filius responsible for the completion of the church could be his follower Innocent I (401–417) as called once by Hieronymus successor et filius (ep. 130, 16 [CSEL 56, 196]) of Anastasius.